The Correlation Between Students’ Learning Interest and Motivation in Speaking - Nanang Sugianto (Jurnal Pendidik Indonesia (JPIn), 2020)
This research was aimed to know the correlation between students learning interest and motivation in speaking at the second student of SMPN 02 Keruak. This research was correlation research with person product moment used quantitative approach. The population of the research was the second grade students of SMPN 02 Keruak. Which consists of five classes. Total sample random sampling technique is used to take the sample of this research because the researcher takes one class. There were 30 students at second grade student of SMPN 02 Keruak as the sample. The data was collated by using questionnaire were analyzed by person product moment, linier regression, and t-test. From the data analysis, the results of the study to indicate that the independent variables of learning interest have positive influence whit motivation to encourage speaking ability in the second grade of SMPN 02 Keruak. Based on the results of the Pearson product moment correlation test (r test), learning interest has a correlation with motivation in encouraging students' speaking ability, which is indicated by a significance value below 0.05, which means that it is significant and based on the results of the t-test results of the variable learning. Motivation to encourage speaking ability obtained test results of 2,313 1,701).the researchers came to conclusion that the hypothesis set is Accepted (Ha). From the result of data analysis above, the researchers concluded that Learning Interest has a significant effect both partial on the motivation to speaking.